Influence of intensive etching processes on structure and properties of carbon nitride films - Shalaev, R.V.; Varyukhin, V.N.; Prudnikov, A.M.; Linnik, A.I.; Zhikharev, I.V.; Belousov, N.N.; Raspornya, D.V.; Ulyanov, A.N. (Functional Materials, 2008)
The influence of electromagnetic radiation and oxygen impurity in the growth atmosphere on the growth processes of nanostructured carbon nitride CNx films has been studied. The oxygen impurity in the gas mixture and an UV irradiation has been found to decrease the thickness and refraction index of carbon nitride films, while increasing the optical band gap width. The intensive etching processes result in the formation of closepacked columnar film nanostructures of carbon nitride.